2018
DOI: 10.1038/s41401-018-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of predominant GNPTAB gene mutations in Eastern Chinese patients with mucolipidosis II/III and a prenatal diagnosis of mucolipidosis II

Abstract: Mucolipidosis II α/β, mucolipidosis III α/β, and mucolipidosis III γ are autosomal recessive disorders belonging to the family of lysosomal storage disorders caused by deficiency of the UDP-N-acetylglucosamine, a lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (GlcNAc-phosphotransferase) localized in the Golgi apparatus, which is essential for normal processing and packaging of soluble lysosomal enzymes with initiating the first step of tagging lysosomal enzymes with mannose-6-phosphate (M6P). Mucoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Whereas the Trp 357 , Leu 358 , Leu 380 , Ile 392 , Ile 395 , Leu 398 , and Phe 420 residues in the CR2 domain may be crucial for intermolecular and/or intramolecular hydrophobic interactions of GlcNAc‐1‐phosphotransferase, the conformation of Pro 355 and Pro 381 may stabilize the molecular structure of the enzyme and, in particular, of the CR2 domain (Dill, ). Most importantly, among conserved residues within the stealth domains, missense mutations leading to amino acid substitutions of Glu 389 , Asp 408 , His 956 , and Arg 986 have been identified in individuals affected by MLII and MLIII alpha/beta, that is, p.Glu389Lys (Velho et al, ), p.Asp408Asn (Wang et al, ), p.His956Tyr (Otomo et al, ), p.His956Arg (Cathey et al, ), p.Arg986Cys (Cobos, Steglich, Santer, Lukacs, & Gal, ; Coutinho et al, ), p.Arg986Gly (Velho et al, ), and p.Arg986His (Mistri et al, ). The clinical description and the molecular analysis of the patient with severe MLII harboring the homozygous mutation p.Glu389Lys (Velho et al, ) have become available and are presented here for the first time (Supporting Information).…”
mentioning
confidence: 99%
“…Whereas the Trp 357 , Leu 358 , Leu 380 , Ile 392 , Ile 395 , Leu 398 , and Phe 420 residues in the CR2 domain may be crucial for intermolecular and/or intramolecular hydrophobic interactions of GlcNAc‐1‐phosphotransferase, the conformation of Pro 355 and Pro 381 may stabilize the molecular structure of the enzyme and, in particular, of the CR2 domain (Dill, ). Most importantly, among conserved residues within the stealth domains, missense mutations leading to amino acid substitutions of Glu 389 , Asp 408 , His 956 , and Arg 986 have been identified in individuals affected by MLII and MLIII alpha/beta, that is, p.Glu389Lys (Velho et al, ), p.Asp408Asn (Wang et al, ), p.His956Tyr (Otomo et al, ), p.His956Arg (Cathey et al, ), p.Arg986Cys (Cobos, Steglich, Santer, Lukacs, & Gal, ; Coutinho et al, ), p.Arg986Gly (Velho et al, ), and p.Arg986His (Mistri et al, ). The clinical description and the molecular analysis of the patient with severe MLII harboring the homozygous mutation p.Glu389Lys (Velho et al, ) have become available and are presented here for the first time (Supporting Information).…”
mentioning
confidence: 99%
“…The results presented here are the first to analyze the consequences of missense mutations within the N‐terminal TMD of GlcNAc‐1‐phosphotransferase that were recently identified in patients with MLII/MLIII αβ (Velho et al, 2019; Wang et al, 2019). Our data establish that two of the mutations, namely p.Val27Asp and p.Val28Asp, that cause the more severe form of the disease (MLII), prevent the insertion of the nascent polypeptide chain into the ER lumen and have no detectable enzyme activity.…”
Section: Discussionmentioning
confidence: 96%
“…Though our study clearly reveals two distinct mechanisms that contribute to the pathogenicity of these mutations, a correlation of our functional data with the clinical outcome of the individual patients is not precise. For instance, both the p.Ala34Pro and p.Glu36Pro mutants are poorly retained in the Golgi and display around 20% GlcNAc‐1‐phosphotransferase activity compared to WT, yet the patient with the p.Ala34Pro mutation was diagnosed with MLII (Wang et al, 2019), whereas the patient with the p.Glu36Pro mutation was diagnosed with MLIII αβ (Velho et al, 2019). In the case of the former, it was reported that the second GNPTAB allele of the patient also had a mutation (c.136C>T; p.Arg46X) which resulted in the codon for arginine changing into a termination codon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLII is characterized by neonatal onset of coarse facial features, restricted postnatal growth, generalized hypotonia, gingival hypertrophy and multiple skeletal abnormalities including thoracic deformity, clubfeet, long bone deformity, hip dislocation, and cardiac valvular abnormalities [ 1 , [10] , [11] , [12] , [13] , [14] ]. MLIIIα/β is a later-onset form which is typically diagnosed around three years of age and has slower progression [ 1 , [10] , [11] , [12] , [13] , [14] ]. Those with MLIIIα/β typically live into early adulthood, while most patients with MLII die in early childhood, usually with respiratory compromise [ 15 ].…”
Section: Introductionmentioning
confidence: 99%